Răspuns :
a:b=3 rest 4
a=3b+4
2a+b=43
2*(3b+4)+b=43
6b+8+b=43
7b+8=43
7b=43-8
7b=35
b=35:7
b=5
a=3*5+4
a=15+4
a=19
a=3b+4
2a+b=43
2*(3b+4)+b=43
6b+8+b=43
7b+8=43
7b=43-8
7b=35
b=35:7
b=5
a=3*5+4
a=15+4
a=19
din datele problemei stim ca:
a:b=3 rest 4
2a+b=43
deci, a=3b+4
inlocuim necunoscutele si obtinem:
2x(3b+4)+b=43
6b+8+b=43
7b+8=43
7b=43-8
7b=35
b=35:7
b=5
aflam si cealalta necunoscuta:
2a+b=43
2a+5=43
2a=43-5
2a=38
a=38:2
a=19
proba:
19:5=3 rest 4
2x19+5=38+5=43
a:b=3 rest 4
2a+b=43
deci, a=3b+4
inlocuim necunoscutele si obtinem:
2x(3b+4)+b=43
6b+8+b=43
7b+8=43
7b=43-8
7b=35
b=35:7
b=5
aflam si cealalta necunoscuta:
2a+b=43
2a+5=43
2a=43-5
2a=38
a=38:2
a=19
proba:
19:5=3 rest 4
2x19+5=38+5=43